2022
DOI: 10.3390/ijms23179515
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Lipase ROL to Increase Its Thermostability for Production of Structured Tags

Abstract: 1,3-regiospecific lipases are important enzymes that are heavily utilized in the food industries to produce structured triacylglycerols (TAGs). The Rhizopus oryzae lipase (ROL) has recently gained interest because this enzyme possesses high selectivity and catalytic efficiency. However, its low thermostability limits its use towards reactions that work at lower temperature. Most importantly, the enzyme cannot be used for the production of 1,3-dioleoyl-2-palmitoylglycerol (OPO) and 1,3-stearoyl-2-oleoyl-glycero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Our results indicated that enhancing the thermostability and catalytic activity of ROL through N-glycosylation was equally effective. 32 This approach can be efficiently combined with other non-N-glycosylation modification strategies, thereby developing high-performance biocatalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that enhancing the thermostability and catalytic activity of ROL through N-glycosylation was equally effective. 32 This approach can be efficiently combined with other non-N-glycosylation modification strategies, thereby developing high-performance biocatalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we have with this work demonstrated that a pro region is required for efficient secretion and strain stability, and that both pro-ROL or pro-Lip2 could be used for ROL production. In contrast, the pro-ROL region was not used for the expression of ROL in Pichia pastoris by Chow and Nguyen (Chow and Nguyen 2022 ), who used the Saccharomyces cerevisiae prepro region of the alpha factor. Using the strong methanol-inducible AOX1 promoter for ROL production, they could produce wild-type and thermostable variants of ROL at 40 to 120 mg/L in P. pastoris .…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequences for the selected proteins were taken directly from these reports (Supplementary Data 2). As RoL-WT could not be expressed in E. coli, a previously described mutant which had previous successful E. coli expression (RoL10X) was used 108 . The Ser-His-Asp (SHD) hydrolase group of enzymes was selected from our in-house PET hydrolase library, including two previously reported thermostabilized variants, LCC-ICCG and HotPETase 21,58 .…”
Section: Enzyme Identification and Homology Searchesmentioning
confidence: 99%